2014
DOI: 10.1519/jsc.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Interunit Reliability of 10 Hz and 15 Hz GPS Units for Assessing Athlete Movement Demands

Abstract: Johnston, RJ, Watsford, ML, Kelly, SJ, Pine, MJ, and Spurrs, RW. Validity and interunit reliability of 10 Hz and 15 Hz GPS units for assessing athlete movement demands. J Strength Cond Res 28(6): 1649-1655, 2014-The purpose of this study was to assess the validity and interunit reliability of 10 Hz (Catapult) and 15 Hz (GPSports) Global Positioning System (GPS) units and investigate the differences between these units as measures of team sport athlete movement demands. A team sport simulation circuit was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
270
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(285 citation statements)
references
References 23 publications
(61 reference statements)
10
270
3
2
Order By: Relevance
“…The 10 Hz GPS units used in this study have previously been shown to be more reliable than 5 and 15 Hz GPS (25,36). The GPS units used have a typical error (expressed as coefficient of variation; CV) of 1.9, 4.7 and 10.5% for total distance, high-speed running (>4.7 m.s -1 ) and very high-speed running (>5.56 m.s -1 ), respectively (36).…”
Section: Methodsmentioning
confidence: 91%
“…The 10 Hz GPS units used in this study have previously been shown to be more reliable than 5 and 15 Hz GPS (25,36). The GPS units used have a typical error (expressed as coefficient of variation; CV) of 1.9, 4.7 and 10.5% for total distance, high-speed running (>4.7 m.s -1 ) and very high-speed running (>5.56 m.s -1 ), respectively (36).…”
Section: Methodsmentioning
confidence: 91%
“…The device has been reported to be both reliable and valid in previous studies. 10,12 The team completed four to seven sessions per week, with a mean of 75.1 ± 23.5 minutes played per match and training session duration of 68.5 ± 17.3 minutes. All of the observed training sessions were designed by the team's head coach and sport scientist.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…GPS technology has improved over the last several years 9 and evidence indicates that GPS data can provide a viable estimate of external training loads imposed on athletes in team sports. [10][11][12] In order to improve measurements of change-of-direction and contact activities, GPS units have been equipped with additional gyroscope and triaxial accelerometer technology. 13 The information provided from GPS is much more objective compared to session RPE.…”
Section: Introductionmentioning
confidence: 99%
“…The primary locomotive demand analysed from the GPS data was total distance, which has previously been proven reliable (Johnston et al, 2014).…”
mentioning
confidence: 99%